Math, asked by manishasanghvi26, 4 months ago

I x²
x - x - (2 + √2 ) x + √2​

Answers

Answered by angelangelmansha02
0

Answer:

We know that (x²+x-2)²=(x-1)(x+2)

Therefore

[(x-1)(x+2)]²=x(x+2)²

=>

(x-1)²(x+2)²=x(x+2)²

=>

(x-1)²(x+2)²-x(x+2)² =0

(x+2)² [(x-1)² - x] =0

x+2 =0 or (x-1)² - x =0

We have : (x-1)² - x =0 =>

(x² - 2x -x +1 =0 => Δ = 9- 4 =5

X2= [3+ sqrt(5)]/2 .

X3= [3- sqrt(5)]/2 and

Answered by AxionNeX
0

Step-by-step explanation:

3-sqrt(5/2) hope it helps

Similar questions